CONSIDERATIONS ON THE POSSIBLE EFFECTS OF DECENTRALIZATION IN PUBLIC SERVICE ADMINISTRATION: THE CASE OF THE AUTONOMOUS REGIONS IN PUERTO RICO - Cordero Nieves, Yolanda (Estado, Gobierno y Gestión Pública, 2014)
Decentralization has been one of the most common reforms undertaken by democratic governments over the past two decades. The transfer of human resources to subnational levels as part of a decentralization is rarely the main purpose of reform, but is rather a side effect of decentralization. This article discusses the theoretical challenges and then applies them to the case of Puerto Rico, where the feasibility of initiating a process of decentralization of central government responsibilities to an intermediate level between it and municipal governments is evaluated. The existence of a national merit system reflects two different realities: public service at the central level and public service at the municipal level. Finally, the article seeks to clarify the issues that must be addressed by representatives of different government sectors and trade unions.